Activity of entomopathogenic nematodes (Rhabditida) against cereal leaf beetle (Oulema melanopus [L.], Coleoptera, Chrysomelidae) adults under laboratory conditions - Žiga LAZNIK; Melita ŠTRUKELJ; Stanislav TRDAN (Acta Agriculturae Slovenica)
In 2009, three Slovenian strains of entomopathogenic nematodes) and commercial product Entonem (active ingredient S. feltiae), were tested under laboratory conditions for their activity against adult cereal leaf beetles (Oulema melanopus). The nematode strains were tested at four different doses (250, 500, 1000, and 2000 infective juveniles/adult) and at three temperatures (15, 20, and 25 ?C). Steinernema carpocapsae strain C101 was the most effective and showed itself to be a good alternative to chemical insecticides, and appears to have the highest potential for controlling overwintered cereal leaf beetles under field conditions. In our bioassay the temperature had the greatest influence on the efficacy of the entomopathogenic nematode strains; both S. feltiae treatments (strain B30 and Entonem) proved to work better at the lowest temperature, however the strain H. bacteriophora D54 had its best efficacy at the highest temperature in the experiment. Several species (S. feltiae and S. carpocapsae) have been efficient at lower suspension concentrations, which enables their economical usage against the cereal leaf beetle in integrated cereal production in the future.